Clinical Significance of Peripheral Arterial Disease Evaluation in Patients with Antineutrophil Cytoplasmic Antibody-Associated Vasculitis - Jeong Yeop Whang; Lucy Eunju Lee; Jang Woo Ha; Oh Chan Kwon; Yong-Beom Park; Sang-Won Lee (Medicina)
Background and Objectives: This study investigated the frequency and clinical significance of subclinical but substantial peripheral arterial disease (PAD), identified using PAD evaluation, including pulse volume recording/ankle–brachial index (PVR/ABI), transcutaneous oxygen pressure (TcpO2), and skin perfusion pressure (SPP) tests in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Materials and Methods: This study included 54 patients with PAD evaluation results at or after AAV diagnosis. PVR/ABI and/or TcpO2 and/or SPP were performed on the same day. Abnormal PVR/ABI, TcpO2, and SPP were defined as PVR/ABI < 0.97, TcpO2 < 40 mmHg, and SPP < 50 mmHg, respectively. Poor outcomes included all-cause mortality, end-stage kidney disease (ESKD), cerebrovascular accidents, and acute coronary syndrome after PAD evaluation. Results: The median age of the 54 patients was 67 years, and 48.1% were male. In total, 3 of 54 patients (5.6%), 6 of 16 (37.5%), and 6 of 23 (26.1%) had abnormal PVR/ABI, TcpO2, and SPP, respectively. The concordance rate between abnormal PVR/ABI and abnormal TcpO2 or SPP was very low. Among the 54 patients, 5 (9.3%) died, and 2 (3.7%) progressed to ESKD. Abnormal SPP was significantly associated with cutaneous and renal manifestations at the time of PAD evaluation and had the potential to predict progression to ESKD during follow-up in patients with AAV. Conclusions: This study is the first to reveal the clinical usefulness of PAD evaluation: abnormal SPP may have the potential to identify subclinical but substantial PAD and can predict simultaneous kidney involvement as well as future progression to ESKD in patients with AAV.